Exploration of the attitude towards African American vernacular English and its speakers by students of foreign languages (2021)
This study aimed to find out what perceptions about AAVE (African American Vernacular English) and its speakers were upheld by Foreign Languages students at Universidad del Valle. Students from all of the English courses and some students that were not taking the English course anymore were presented with a survey where they had to distinguish four sentences containing AAVE features. In a Likert scale, they had to rate the dialect on its proximity to standard English and the speakers on personality and demographic characteristics. According to the results, students were not able to recognize the dialect and they see it as different to the standard. When it comes to their opinions about the speakers it was found that they are mostly neutral to positive although it was noted that students in the lowest levels are more likely to give negative ratings.